Political Law of Sidawangi Society towards Customary Rights Over Oro-Oro Land - Sarip Sarip; Hanif Nurcholish Adiantika; Abdul Muaz (Universitas Lampung, 2019)
The study concerning political law of Sidawangi society towards customary right over “Oro-Oro” land is commonly triggered by the presence of the arbitrary village officers. Historically, “Oro-Oro” land is characterised as a communal land, but its management is initiated exclusively through an agreement and doubtful rights. The legal law concerning customary right over “Oro-Oro” land is truly expected by Sidawangi society. The action of arbitrary village officers is deemed to be one of crucial factors to realise their expectation.Furthermore, the rumour of switching “Oro-Oro” land into plantation land by the corporation also toughens the strong desire of Sidawangi society to realize their expectation. The present study aims to investigate the significance of legal law and the warranty of customary rights both in the 1945 Constitution, agrarian law and international conventions. This study is conducted through an interview to Sidawangi society and literature studies regarding customary right over “Oro-Oro” land as expected by Sidawangi society. Customary right over “Oro-Oro” land, initiated by Sidawangi Society in Sumber Sub-District, originally refers to a communal area which has been exclusively possessed. In other words, this type of land is not privately preserved. The people in Sidawangi society are only allowed to maintain and gather the result. The arbitrary of village officers seize trees in “Oro-Oro” land without any kinds of certain customary right. The phenomenon in Lampung has provided insight regarding the conflict occurs when the people expect is not fulfilled. The residents inevitably expect the existence of political law in society towards customary land. The legal protection towards customary right over “Oro-Oro” land is essentially guaranteed by 1945 constitution, Basic Agrarian Law Constitution, and international convention of indigenous community.